2022
DOI: 10.1111/cup.14309
|View full text |Cite
|
Sign up to set email alerts
|

Linear IgA bullous dermatosis in the setting of angioimmunoblastic T‐cell lymphoma

Abstract: We report an 80‐year‐old male developing linear IgA bullous dermatosis (LAD) in the setting of angioimmunoblastic T‐cell lymphoma (AITL). This phenomenon is rare, as only three cases have been described in the literature. The pathophysiologic process can be attributed to dysregulation in somatic hypermutation and the expression of chemokine receptor 5 in AITL, contributing to increased IgA. Immunoglobulin production resulting from clonal plasma cell expansion may be because of the B‐cell promotional effect by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Among malignancies, the association between hematologic malignancies and LABD is more established than that with solid organ tumors. Andriano et al reported a case of LABD in the setting of angioimmunoblastic T-cell lymphoma (AITL) and explained the pathophysiological process of dysregulation of somatic hypermutation and expression of chemokine receptor 5 in AITL, which leads to increased IgA [33]. Colmant et al reported that a case of LABD associated with cutaneous involvement of an angioimmunoblastic T-cell lymphoma showed deep cutaneous involvement of the lymphoma with sub-epidermal blistering and direct immunofluorescence of heavy IgA linear deposits at the dermal-epidermal junction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Among malignancies, the association between hematologic malignancies and LABD is more established than that with solid organ tumors. Andriano et al reported a case of LABD in the setting of angioimmunoblastic T-cell lymphoma (AITL) and explained the pathophysiological process of dysregulation of somatic hypermutation and expression of chemokine receptor 5 in AITL, which leads to increased IgA [33]. Colmant et al reported that a case of LABD associated with cutaneous involvement of an angioimmunoblastic T-cell lymphoma showed deep cutaneous involvement of the lymphoma with sub-epidermal blistering and direct immunofluorescence of heavy IgA linear deposits at the dermal-epidermal junction [34].…”
Section: Discussionmentioning
confidence: 99%